PENGARUH PRESTASI BELAJAR PERENCANAAN PENGAJARAN DAN MICRO TEACHING TERHADAP PRAKTIK PENGALAMAN LAPANGAN MAHASISWA PENDIDIKAN AKUNTANSI IKIP PGRI MADIUN - Supri Wahyudi Utomo (Assets: Jurnal Akuntansi dan Pendidikan, 2012)
This study aimed to determine the effect of teaching and learning achievement planning to practice micro teaching field experience accounting education collage students IKIP PGRI Madiun. The analysis method used is multiple regression. The results showed that the learning achievements and course planning Teaching Micro Teaching simultaneously influence the success in participating in the Practice Field Experience. There is a positive effect between achievement Instructor course on learning achievement Planning Practice Field Experience. However, this study did not find any significant effect between achievement on learning achievement Micro Teaching Practice Practice Field Experience.